Buletin Peternakan : PENGARUH SUPLEMENTASI MINYAK IKAN DAN L-KARNITIN DALAM PAKAN JAGUNG KUNING TERFERMENTASI TERHADAP KECERNAAN PAKAN DAN PERFORMA PUYUH (Coturnix coturnix japonica) - Sinelsa Wulandari Sani, Setiana Rohmi Heswantari, Sudibya, Sutrisno Hadi Purnomo, Aqni Hanifa (Peternakan UGM, 2015)
The research was aimed to determine the effect of fish oil and L-carnitine supplementation in a fermented yellow corn diets on the performance of quail (Coturnix coturnix japonica). The experiment wasÃ‚ used 160 quails aged 70 days that were divided into five treatments and four replications. Each replicationÃ‚ consisted of eight female quails. The mean initial body weight was 156.60Ã‚Â±9.61 g with Coefficient ofÃ‚ Variance (CV) of 6.14%. The in-vivo digestibility study was carried out on the last week using totalÃ‚ collection method. Two quails were chosen randomly from each cage and placed into individual raised cages.